2002
DOI: 10.1002/xrs.546
|View full text |Cite
|
Sign up to set email alerts
|

Quality control of commercial tea by x‐ray fluorescence

Abstract: Based on the energy-dispersive x-ray fluorescence (EDXRF) technique, the concentrations of elements (22 ≤ Z ≤ 30) were assessed in five kinds of commercial tea from six commercial suppliers: Matricaria chamomilla L. (camomile), Mentha piperita L. (mint), Cymbopogon citratus (DC) Stapf. (herb 'cidreira'), Malus domestica Borkh. (apple tea) and Camellia sinensis (L.) O. Kuntze (black tea). The samples were excited by an x-ray tube with an Mo anode (25 kV and 10 mA), with a Zr filter, and the characteristic x-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Analysis of variance of the data showed no statistically significant differences in mean Cr content among the different kinds of tea (p > 0.05). Salvador et al (24) determined Cr presence in black tea, although levels were not detectable. However, Onianwa et al (25) reported values of Cr The mean Mn contents in green, black, and oolong teas were 541.6, 285.9, and 354.0 µg/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of variance of the data showed no statistically significant differences in mean Cr content among the different kinds of tea (p > 0.05). Salvador et al (24) determined Cr presence in black tea, although levels were not detectable. However, Onianwa et al (25) reported values of Cr The mean Mn contents in green, black, and oolong teas were 541.6, 285.9, and 354.0 µg/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, several groups have proposed different conditions to obtain clean herbal water extracts. 23,24,27,28 In traditional medicine and as a common drinking beverage in many Eastern and Oriental countries, the preparation of herbal drinks for oral intake involves cooking the plants with water for 30-90 min. In modern herbal medicine, the herbs are cooked with water or ethanol and then processed into tablets, pills or liquids.…”
Section: Infusion Preparationmentioning
confidence: 99%
“…Generally, the determination of total concentrations of various macro-and micro-elements in different teas as well as medicinal plants is carried out with the use of flame atomic absorption spectrometry (FAAS) (Aksuner et al 2012;Colak et al 2005;Kumar et al 2005;Li et al 2006;Malik et al 2008;Narin et al 2004a,b;Seenivasan et al 2008;Soylak et al 2007), graphite furnace atomic absorption spectrometry (GF AAS) (Dash et al 2008;Seenivasan et al 2008), inductively coupled plasma optical emission spectrometry (ICP OES) (Chen et al 2009;Dash et al 2008;Kara 2009;Malik et al 2008;Matsuura et al 2001;McKenzie et al 2010;Mierzwa et al 1998;Özcan et al 2008), inductively coupled plasma mass spectrometry (ICP MS) (Kara 2009;Matsuura et al 2001;Nookabkaew et al 2006;Shen and Chen 2008) and X-ray fluorescence spectrometry (XRFS) (Salvador et al 2002;Xie et al 1998). As a rule, the decomposition of the matrix of tea samples is an indispensable and mandatory step before their elemental analysis by the majority of these spectrometric methods.…”
Section: Introductionmentioning
confidence: 99%